Pengaruh Critical Success Dalam Implementasi Enterprise Resource Planning (ERP) Terhadap Kinerja Perusahaan Studi Pada PT. Angkasa Pura II (Persero) - Rezi Eka Putra (Akuntabilitas, 2018)
This study aims to determine the effect of the critical success factor in the implementation of enterprise resource planning (ERP) and company performance study at PT Angkasa Pura II (Persero). Critical success factor was measured by using a variable business process reengineering (BPR), education and training (DIKLAT), and support suppliers (VENDOR) towards success ERP implementation (KIMP). The company's performance is measured by looking at the net benefit of implementing ERP systems for companies (NETB). The result of Lisrel 8.8 has an analysis that shown to business process reengineering (BPR = 2.41), education and training (DIKLAT = 5.53), support suppliers (VENDOR = 4.30) has a positive influence on the successful implementation of ERP (KIMP), and the successful implementation of ERP (KIMP = 10.10) positively influences to net benefit of implementing ERP systems for companies (NETB).